IMPLIKASI HUKUM-BISNIS KEBIJAKAN PAJAK IMPOR DAN RELAKSASI TKDN TERHADAP KONTRUKSI - Oktaviani, Putri (Ensiklopedia Education Review, 2025)
Abstract: Global import tax policies and the planned relaxation of the Domestic Component Level (TKDN) have significant impacts on Indonesia's construction sector. Amidst a global trend of protectionism marked by rising import tariffs imposed by major economies, national contractors face serious challenges due to their reliance on imported raw materials and capital goods. On the other hand, the shift in TKDN policy—from a mandatory approach to an incentive-based one under the Prabowo Subianto administration—creates tension between operational efficiency and national industry protection. The disharmony between foreign trade policies and domestic industrial policies increases the potential for legal uncertainty for construction business actors, who play a strategic role in national development. Using a normative juridical method, this study examines the legal and business implications of these policy dynamics and evaluates the urgency of regulatory harmonization as a foundation for creating a stable, competitive, and sustainable business climate for Indonesia’s construction sector. Keywords: Global Import Tax, TKDN Relaxation, Construction Sector.